A secreted factor NimrodB4 promotes the elimination of apoptotic corpses by phagocytes in Drosophila. - Petrignani, B.; Rommelaere, S.; Hakim-Mishnaevski, K.; Masson, F.; Ramond, E.; Hilu-Dadia, R.; Poidevin, M.; Kondo, S.; Kurant, E.; Lemaitre, B. (EMBO Reports, 2021)
Programmed cell death plays a fundamental role in development and tissue homeostasis. Professional and non-professional phagocytes achieve the proper recognition, uptake, and degradation of apoptotic cells, a process called efferocytosis. Failure in efferocytosis leads to autoimmune and neurodegenerative diseases. In Drosophila, two transmembrane proteins of the Nimrod family, Draper and SIMU, mediate the recognition and internalization of apoptotic corpses. Beyond this early step, little is known about how apoptotic cell degradation is regulated. Here, we study the function of a secreted member of the Nimrod family, NimB4, and reveal its crucial role in the clearance of apoptotic cells. We show that NimB4 is expressed by macrophages and glial cells, the two main types of phagocytes in Drosophila. Similar to draper mutants, NimB4 mutants accumulate apoptotic corpses during embryogenesis and in the larval brain. Our study points to the role of NimB4 in phagosome maturation, more specifically in the fusion between the phagosome and lysosomes. We propose that similar to bridging molecules, NimB4 binds to apoptotic corpses to engage a phagosome maturation program dedicated to efferocytosis.